2000
DOI: 10.1093/hmg/9.11.1603
|View full text |Cite
|
Sign up to set email alerts
|

A neonatal lethal mutation in FGFR3 uncouples proliferation and differentiation of growth plate chondrocytes in embryos

Abstract: We have generated the first mouse model of fibro-blast growth factor receptor 3 (Fgfr3) with the K644E mutation, which accurately reflects the embryonic onset of a neonatal lethal dwarfism, thanatophoric dysplasia type II (TDII). Long-bone abnormalities were identified as early as embryonic day 14, during initiation of endochondral ossification. Increased expression of PATCHED: (PTC:) was observed, independent of unaltered expression of parathyroid hormone-related peptide (PTHrP) receptor and Indian Hedgehog (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
147
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 56 publications
14
147
1
2
Order By: Relevance
“…Many of the common forms of dwarfim are caused by activating mutations in Fgfr3 (Naski et al, 1998), suggesting that in the growth plate of long bones, FGFR3 is a negative regulator of chondrocyte proliferation. However, Iwata et al reported that signaling through FGFR3 can both promote and inhibit chondrocyte proliferation depending on the stage of development (Iwata et al, 2000). FGF-18 signaling through FGFR3 may enhance chondrocyte proliferation in immature committed chondrocytes, even though it is well established that signaling through FGFR3 inhibits chondrocyte proliferation and differentiation in the mature proliferating chondrocyte zone of the growth plate (Ellsworth et al, 2002;Liu et al, 2002).…”
Section: (B) Extracellular Signaling Mediated By Fgf-18mentioning
confidence: 99%
“…Many of the common forms of dwarfim are caused by activating mutations in Fgfr3 (Naski et al, 1998), suggesting that in the growth plate of long bones, FGFR3 is a negative regulator of chondrocyte proliferation. However, Iwata et al reported that signaling through FGFR3 can both promote and inhibit chondrocyte proliferation depending on the stage of development (Iwata et al, 2000). FGF-18 signaling through FGFR3 may enhance chondrocyte proliferation in immature committed chondrocytes, even though it is well established that signaling through FGFR3 inhibits chondrocyte proliferation and differentiation in the mature proliferating chondrocyte zone of the growth plate (Ellsworth et al, 2002;Liu et al, 2002).…”
Section: (B) Extracellular Signaling Mediated By Fgf-18mentioning
confidence: 99%
“…FGFs bind to and activate this receptor and cause growth arrest in chondrocytes, leading to short limbs. Early studies also suggested that FGFs inhibit chondrocyte differentiation [Iwata et al, 2000], although this hypothesis has been challenged by more recent studies. Minina et al [2002] using an organ culture from embryonic limb explants, has demonstrated that FGF2 reduced the rate of chondrocyte proliferation, as well as promoting chondrocyte hypertrophic differentiation as indicated by the shorter distance between the joint and hypertrophic chondrocytes.…”
Section: Inhibitors Of Ihh Expressionmentioning
confidence: 99%
“…Fgfr3-null mice are viable, however they exhibited prolonged and faster growth of long bones (Colvin et al, 1996;Deng et al, 1997). Conversely, introduction of constitutively activated mutations into Fgfr3 results in dominant dwarfism due to retarded long bone growth (Chen et al, , 2001Iwata et al, 2000;Li et al, 1999). Fgfr4-null mice exhibit depleted gallbladders and have elevated cholesterol metabolism and bile acid synthesis (Yu et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%